2009
DOI: 10.1101/lm.1154409
|View full text |Cite
|
Sign up to set email alerts
|

Systemic or intra-amygdala injection of a benzodiazepine (midazolam) impairs extinction but spares re-extinction of conditioned fear responses

Abstract: Rats were subjected to one or two cycles of fear conditioning and extinction, injected with a benzodiazepine, midazolam, before the first or second extinction, and tested for long-term inhibition of fear responses (freezing). In Experiment 1, inhibition of context-conditioned fear was spared when midazolam was injected before the second extinction, but impaired when injected before the first. In Experiment 2, it was spared when midazolam was injected before the second extinction, but only if vehicle had been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 28 publications
2
42
0
Order By: Relevance
“…Experiment 1 replicated the previous findings of Hart et al (2009) that rats re-extinguished for 20 min under midazolam (Group Re-Ext 20min MID) failed to show impairment on the subsequent retention test, exhibiting low levels of fear similar to those shown by rats reextinguished for 20 min under vehicle (Group Re-Ext 20min VEH). Experiment 1 revealed a novel finding: Rats reextinguished for just 4 min under midazolam (Group Re-Ext 4min MID) also showed low levels of fear on the retention test, suggesting that long-term inhibition had been just as effective with a short, as with a longer, re-extinction session.…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…Experiment 1 replicated the previous findings of Hart et al (2009) that rats re-extinguished for 20 min under midazolam (Group Re-Ext 20min MID) failed to show impairment on the subsequent retention test, exhibiting low levels of fear similar to those shown by rats reextinguished for 20 min under vehicle (Group Re-Ext 20min VEH). Experiment 1 revealed a novel finding: Rats reextinguished for just 4 min under midazolam (Group Re-Ext 4min MID) also showed low levels of fear on the retention test, suggesting that long-term inhibition had been just as effective with a short, as with a longer, re-extinction session.…”
Section: Methodssupporting
confidence: 78%
“…The design (see Table 1) consisted in subjecting rats to two context conditioning episodes, a brief (4 min) or longer (20 min) extinction under the drug or vehicle, and finally, a retention test. Hart et al (2009) have shown that rats given 20-min extinction under midazolam exhibited substantial levels of fear responses on the subsequent retention test, suggesting that the drug had disrupted learning inhibition. But we have not previously examined whether rats subjected to a shorter (e.g., 4 min) extinction under the drug also show substantial levels of fear responses on the subsequent test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These neurons project to diencephalic and brainstem structures that control the behavioral, autonomic, and endocrine components of the fear response (Sah et al 2003). In addition to its key role in fear learning, the BLA is also necessary for acquisition and consolidation of extinction (Lin et al 2003;Herry et al 2006Herry et al , 2008Kim et al 2007;Sotres-Bayon et al 2007Kim and Richardson 2008;Hart et al 2009). Recent evidence (Herry et al 2008) has revealed that a distinct population of BLA neurons contributes to the inhibitory learning produced by extinction.…”
Section: Discussionmentioning
confidence: 99%
“…This view has received support from recent studies of the neural mechanisms underlying relearning to inhibit fear responses (Kim and Richardson 2008;Hart et al 2009). Relearning occurs when an extinguished CS is paired with the aversive US and the fear responses produced by that retraining are again extinguished.…”
mentioning
confidence: 96%